Self Help Group (SHG) sebagai Salah Satu Strategi Intervensi Mengendalikan Tekanan Darah bagi Penderita Hipertensi - R. Siti Maryam (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
Self-help group is a collection some of the people who provide mutual support among them. In the group they can share the problems especially about the disease. Hypertension is one of the diseases that cause death number 3 after stroke and tuberculosis .This is reinforced by the prevalence of hypertension in Indonesia reached 31.7% of the population aged 18 years and over. And 60% of them end up in the stroke, while the rest suffered cardiac, kidney failure, and blindness. Hypertension risk factors such as stress, obesity, lack of exercise, smoking, drinking alcohol, and eating foods high in fat content to be a problem for some people if it does not know how to overcome them.Therefore, the purpose of the self - help group is to help each other deal with the same problems, more away is to cure, then the active participation of individuals and families need to realize.